2014
DOI: 10.1038/labinvest.2014.6
|View full text |Cite
|
Sign up to set email alerts
|

Tapasin modification on the intracellular epitope HBcAg18–27 enhances HBV-specific CTL immune response and inhibits hepatitis B virus replication in vivo

Abstract: HBV-specific cytotoxic T-lymphocyte (CTL) activity has a very important role in hepatitis B virus clearance. Present studies suggest that Tapasin, a endoplasmic reticulum (ER) chaperone, stabilizes the peptide-receptive MHC I conformation, allowing peptide exchange and increasing more peptides to be translocated into the ER. We have previously testified that cytoplasmic transduction peptide (CTP)-HBcAg 18-27 -Tapasin fusion protein could enter cytoplasm of dendritic cells, and enhance T cells' response to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…The JAK/STAT signaling pathway mediates the biological responses induced by numerous cytokines, and it is particularly important for differentiation of helper T-cells. Cytokines bind to the cell surface receptors of immune and non-immune cells to activate the JAK-STAT signaling pathway, which affects the function of CD4 -T-cells by upregulating the expression of specific target genes (44)(45)(46). In the present study, assays were performed to detect the levels of T-cell cytokines in serum samples and JAK/STAT pathway proteins in the PBMCs of all patients with IgAN prior to treatment and in the healthy control group (49 healthy subjects were selected as the normal control group) There was no significant difference in sex and age between the patients with IgAN and the control group (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…The JAK/STAT signaling pathway mediates the biological responses induced by numerous cytokines, and it is particularly important for differentiation of helper T-cells. Cytokines bind to the cell surface receptors of immune and non-immune cells to activate the JAK-STAT signaling pathway, which affects the function of CD4 -T-cells by upregulating the expression of specific target genes (44)(45)(46). In the present study, assays were performed to detect the levels of T-cell cytokines in serum samples and JAK/STAT pathway proteins in the PBMCs of all patients with IgAN prior to treatment and in the healthy control group (49 healthy subjects were selected as the normal control group) There was no significant difference in sex and age between the patients with IgAN and the control group (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that tapasin modification on the intracellular epitope HBcAg 18-27 via CTP could enter the cytoplasm of BMDCs, thus promoting BMDC maturation, and efficiently enhancing the T-cell immune response in vitro (1). Furthermore, the CTP-HBcAg 18-27 -Tapasin fusion protein was able to enhance the percentage of CTLs, induce robust specific CTL activity, reduce apoptosis of CD8 + T cells and inhibit HBV replication in vivo (10,11). These findings suggested that tapasin may be a key factor in the process of HBV clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that the expressed and purified fusion protein cytoplasmic transduction peptide (CTP)-HBV core antigen (HBcAg) 18-27 -Tapasin could enter the cytoplasm of bone marrow-derived dendritic cells (BMDCs), promoting BMDC maturation and efficiently enhancing the T-cell immune response in vitro (1). Furthermore, the CTP-HBcAg 18-27 -Tapasin fusion protein could enhance the percentage of CTLs, induce robust specific CTL activity, reduce apoptosis of CD8 + T cells and inhibit HBV replication in vivo (10,11). It has also been demonstrated that chronic HBV (CHB) infection is associated with reduced antigen-presenting capacity and insufficient CTL production (12).…”
Section: Introductionmentioning
confidence: 99%
“…CD4 + T cells, including Treg and effector Th cells, play a key role in the host defense. However, the imbalance of CD4 + T cell differentiation leads to chronic infections as well as a variety of inflammatory allergic and autoimmune diseases, such as chronic hepatitis B virus infection (25), rhinallergosis (26) and IgAN (27). The differentiation and functions of CD4 + T cell subsets are dependent upon the cytokine environment, which enables the differentiation into several distinct subtypes to coordinate the immune response to clear the pathogenic insult.…”
Section: T Lymphocyte Classificationmentioning
confidence: 99%